An Analysis of Factors Affecting Consumers in Purchasing Decision of Indocafe Powder Coffee at PT. Sari Tanjungtera Cipta in Bengkulu - Ajeng Fitriani; Ida Anggriani; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the most dominant factor affecting the purchasing decision of Indocafe powder coffee at PT. Sari Tanjung Tera Cipta in Bengkulu. Samples in this study were 37 outlets that purchased Indocafe powder coffee products at PT. Sari Tanjung Tera Cipta in Bengkulu City, especially the Bengkulu route. The data collection method used a questionnaire and the analytical method used was rating scale analysis. The results of this study indicate the average value of respondents' responses to the factors that affect purchasing decisions at PT. Sari Tanjung Tera Cipta in Bengkulu City is 1,474 with the assessment criteria agree. This means that respondents have an agreed assessment of the factors that affect purchasing decisions at PT. Sari Tanjung Tera Cipta in Bengkulu City is affected by cultural, social, personal and psychological factors. Personal factors are the highest factors influencing purchasing decisions online at PT. Sari Tanjung Tera Cipta in Bengkulu City with a score of 1,573. This illustrates that customers shop at PT. Sari Tanjung Tera Cipta in Bengkulu City because because they choose to shop on the basis of their own wishes, PT. Sari Tanjung Tera Cipta in Bengkulu City provides maximum service therefore customers feel satisfied. The lowest factor is the cultural factor with a total score of 1.342 with the assessment criteria agreed. This illustrates that cultural factors have a low affect on purchasing decisions at PT. Sari Tanjung Tera Cipta in Bengkulu City because shopping is a desire not because it is affected by the environment, culture or other people.